Polyamines inhibit the assembly of stress granules in normal intestinal epithelial cells regulating apoptosis - Zou, Tongtong (American Physiological Society, 2012)
Polyamines regulate multiple signaling pathways and are implicated in many aspects of cellular functions, but the exact molecular processes governed by polyamines remain largely unknown. In response to environmental stress, repression of translation is associated with the assembly of stress granules (SGs) that contain a fraction of arrested mRNAs and are thought to function as mRNA storage. Here we show that polyamines modulate the assembly of SGs in normal intestinal epithelial cells (IECs) and that induced SGs following polyamine depletion are implicated in the protection of IECs against apoptosis. Increasing the levels of cellular polyamines by ectopic overexpression of the ornithine decarboxylase gene decreased cytoplasmic levels of SG-signature constituent proteins eukaryotic initiation factor 3b and T-cell intracellular antigen-1 (TIA-1)-related protein and repressed the assembly of SGs induced by exposure to arsenite-induced oxidative stress. In contrast, depletion of cellular polyamines by inhibiting ornithine decarboxylase with α-difluoromethylornithine increased cytoplasmic eukaryotic initiation factor 3b and TIA-1 related protein abundance and enhanced arsenite-induced SG assembly. Polyamine-deficient cells also exhibited an increase in resistance to tumor necrosis factor-α/cycloheximide-induced apoptosis, which was prevented by inhibiting SG formation with silencing SG resident proteins Sort1 and TIA-1. These results indicate that the elevation of cellular polyamines represses the assembly of SGs in normal IECs and that increased SGs in polyamine-deficient cells are crucial for increased resistance to apoptosis.